A new approach to detect the ground clutter mixed with weather echoes - Yinguang Li; Guifu Zhang; Doviak, Richard J. (2011 IEEE RadarCon (RADAR), 2011)
A Spectrum Clutter Identification (SCI) algorithm has been developed to identify ground clutter mixed with weather signals. The performance of SCI algorithm is shown by applying it to radar data collected by OU-PRIME (University of Oklahoma-Polarimetric Radar Innovation in Meteorology and Engineering) and by comparing its performance to other published approaches.